Determination of the APBD through Regional Head Regulations and its Implications for the Principles of Good Governance: Case Study of Indramayu Regency in 2023 - Farida, Ai Siti; Suhendar, Suhendar (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
This study aims to analyze the enactment of the 2023 Regional Revenue and Expenditure Budget (APBD) in Indramayu Regency without mutual agreement between the Regent and the DPRD, using the principles of Good Governance as the main analytical framework. The research adopts a descriptive qualitative approach with a normative analysis of statutory regulations and official government documents. The findings reveal that although the enactment of the APBD through a Regent Regulation is legally justified under Article 313 of Law No. 23 of 2014 and its derivatives, the practice reflects institutional dysfunction, centralization of executive authority, and violations of the principles of participation, transparency, and accountability. The absence of administrative sanctions from the provincial government also indicates weak enforcement of the rule of law and insufficient vertical oversight. This study recommends strengthening collaboration between the executive and legislative bodies, ensuring alignment with agreed fiscal planning documents, enforcing sanctions where appropriate, and reforming oversight systems to ensure that local financial governance adheres to democratic, participatory, and accountable Good Governance standards.